Determination of polycyclic aromatic hydrocarbons in suspended solid from Pengkalan Chepa River, Kelantan, Malaysia, based on weather condition - Babaheidari, Seyedreza Hashemi; Zakaria, Mohamad Pauzi; Md. Muslim, Noor Zuhartini (Springer, 2013)
Pengkalan Chepa River is located in the urban area that receives pollution loads from surronding area, sewage treatment and industrial garages and workshops. This research focuses on the determination of PAHs in suspended solid in Pengkalan Chepa River during rainy day, rainy season and sunny day. Total concentrations of PAHs in suspended solid in rainy day ranged from 323.5 to 1,153.1 ng/g while 7,421.2–1,786.71 ng/g in rainy season and 353.7–560.8 ng/g in sunny day.